Layered perovskite oxides and their derivative nanosheets adopting different modification strategies towards better photocatalytic performance of water splitting. (March 2020) - Hu, Yuchao; Mao, Liuhao; Guan, Xiangjiu; Tucker, Kevin Andrew; Xie, Huling; Wu, Xuesong; Shi, Jinwen
Abstract: Photocatalytic water splitting has been extensively studied in the past decades and numerous semiconductors have been proved to be effective photocatalysts. Among them, layered perovskites, which comprise of a large family of layered oxides with different chemical components, are promising materials because of their stable perovskite slabs consisting of multiple metal cations and flexible interlayer galleries that facilitate modification. In this paper, we systematically review a series of modified layered perovskites with enhanced performance of water splitting. A variety of methods have been extensively applied in the modification of layered perovskites. And derivate photocatalysts with higher activity, better stability and lower cost were obtained. For bulk layered perovskites, this article introduces those that have been modified via photocatalyst design（ion doping and pillaring）as well as synthesis procedure and cocatalyst loading improvement. They show optimized chemical composition, crystal structure, specific area, band energy and morphology, which have been extensively proved to be key factors that decide the performance of photocatalysts. Compared with bulk layered perovskites, layered perovskite nanosheets, normally prepared by exfoliation of corresponding bulk parent materials, show largely increased surface area, which is beneficial for charge transfer. Further modification using these nanosheets as building blocks to construct restacked layered photocatalysts with mono-component or multi-components fully utilizes their ultrathin and charged nature. The modified nanosheets display enhanced charge separation and light absorption due to designed band structure and micro-nano structure, offering a promising future direction of photocatalyst design. Graphical abstract: Image 1 Highlights: Modified layered perovskites show better performance of water splitting. Different modification strategies on layered perovskites are summarized. Better performance results from enhanced charge separation and light absorption. Perovskite nanosheets can be utilized as building blocks for efficient hybrids. Combination of different modifications leads to further improved activity.